Growth of 5 Provenances at 6 Months Old Alstonia Scholaris in Sumber Klampok, Bali (Pertumbuhan Lima Provenan Pulai Gading (Alstonia Scholaris) Umur 6 Bulan di Sumber Klampok, Bali) - Mashudi, Mashudi (Forestry Department, University of Muhammadiyah Makassar, 2015)
Alstonia scholaris (L.) R.Br. is one of native and fast growing species in Indonesia. This species is potential for forest plantation. Its wood can be used for boxes, matches, heelpiece, crafts (mask and puppet), pencil slate, and pulp. This paper aims to study the growth of Alstonia scholaris at 6 month old in Sumber Klampok, Bali. This experiment was arranged in a randomized complete block design with provenances as treatment. The research used 5 provenances, i.e. Lombok (NTB), Jayapura (Papua), Solok (West Sumatera), Timor (NTT) and Bali. Material genetic from 46 parent trees were used and we observed 4 seedling of each patent trees with 6 replications. The result showed that provenances of Bali, Lombok dan NTT were the best provenances for survival rate, height, and stem diameter.